2011 IEEE Third International Conference on Cloud Computing Technology and Science 2011
DOI: 10.1109/cloudcom.2011.110
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Orchestration Engine for the Cloud

Abstract: The Cloud is evolving as a cost-effective solution to run services that support a variety of business processes. It is not surprising then that Orchestration as a Service (OaaS) is gaining importance as a means to integrate the many services a typical company runs or outsources in the Cloud. OaaS requires very efficient orchestration engines: the faster they work, the less customers have to pay and the more customers can be served. In this paper, we report on a new orchestration engine; we have performed a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We present the results of metrics collected during the simulation in tables and charts for each integration process. The statistical theory is indicated to analyse data from experiments on performance [54], because it deals with nondeterminism in computational systems, such as runtime systems of integration platforms [55]. We used the variance analysis (ANOVA) and Scott & Knott statistical tests to evaluate the results.…”
Section: Resultsmentioning
confidence: 99%
“…We present the results of metrics collected during the simulation in tables and charts for each integration process. The statistical theory is indicated to analyse data from experiments on performance [54], because it deals with nondeterminism in computational systems, such as runtime systems of integration platforms [55]. We used the variance analysis (ANOVA) and Scott & Knott statistical tests to evaluate the results.…”
Section: Resultsmentioning
confidence: 99%
“…We used the protocols of procedures for controlled experiments in the engineering studies field indicated by [23], [42], and [5]. Besides, we followed the guidelines of literature, which claim that statistical theory must be used to validate results from experiments on performance [20] because the statistic deals adequately with the non-determinism factors present in computational systems, such as run-time systems [16]. Thus, we used ANOVA [41] and Scott & Knott [35] statistical techniques to validate the results.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter, the run‐time system may control both process instances and their internal tasks. The literature shows that the task‐based model offers better performance with a steady stream of data input and lower performance when the input rate increases, although this model is more complex to provide transaction and fault‐tolerance support . This property may take the following values: process‐based, task‐based, or hybrid.…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…At the end, 9 integration platforms were selected to be analysed, cf Table . The chosen platforms were Camel, Guaraná, Fuse, Jitterbit, Mule, Petal, ServiceMix, Spring Integration, and WSO2 . The analyses of the platform was carried out considering books, online documentation, and source code accessible from their web site.…”
Section: Integration Platforms Selectionmentioning
confidence: 99%